Application of Commitment Acceptance Counseling Based on Islamic Values in Improving Student Self-Efficacy - Chairunnisa, Vinda; Nurihsan, Achmad Juntika; Taufik, Agus; Yusniana, Yusi Riksa (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study explores the effectiveness of Acceptance and Commitment Therapy (ACT) integrated with Islamic values in improving college students' self-efficacy. Low self-efficacy often hinders students' academic performance and emotional well-being, highlighting the need for interventions that address both psychological and spiritual dimensions. This study integrates ACT principles, which emphasize acceptance, commitment, and values, with Islamic teachings such as ikhlas, tawakal, and ridha, to create a holistic counseling framework. Using a pretest-posttest quasi-experiment design, the study involved 15 students from the Counseling Program at Al-Washliyah Muslim Nusantara University who had low self-efficacy. The results showed a significant increase in self-efficacy scores in the experimental group, increasing from 48.2 (low) to 72.5 (moderate to high), while the control group showed minimal change from 65.7 to 67.3. Statistical analysis confirmed the significance of these changes with an effect size (Cohen's d) of 0.7439, indicating a large impact. Qualitative responses further highlighted students' positive perceptions of integrating Islamic values into the counseling process. The students noted that the use of Quranic affirmations, such as “Allah does not burden anyone but according to his ability” (QS. Al-Baqarah: 286), provided emotional relief and strengthened their self-confidence. The findings underscore the potential of Islamic value-based ACT to foster psychological flexibility, resilience and self-efficacy. This approach offers a practical framework for counselors to address the challenges faced by Muslim students, by integrating faith-based values with modern therapeutic practices. Future research is recommended to expand its applicability to a wider student population and explore its adaptability to digital counseling platforms.